Phytolith profile cadastre of the most significant and abundant soil types of Hungary IV. - Pető, Ákos; Barczi, Attila (JOURNAL OF LANDSCAPE ECOLOGY, 2011)
The aim of the series that provides an insight to phytolith patterns of the most significant soil types in Hungary is not only to provide baseline data, but to find a connection between soil forming processes and phytolith distribution throughout soil evolution. We intended to consider the impact of mankind, therefore not only soil profiles under natural vegetation, but profiles of plough-lands and graze lands are included in this study. Both of the examined main types – chernozem and solonetz – represent steppe environment and inherit phytolith assemblages of open grassland habitats. The effect of cultivation in chernozems can be seen in the dominance of phytoliths that represent introduced species (e.g. cereals). A chernozem profile examined under natural grass vegetation reflects the phytolith morphotype spectra characteristic of steppe habitats. In case of the solonetz profiles, relation between soil forming processes (e.g. texture differentation caused by clay formation, strong alkalinization) and phytolith distribution was detected. These soil properties significantly modified vertical phytolith distribution patterns. Base line data provided here may form the basis of indicative phytolith morphotype spectra of characteristic steppe vegetation and habitats, however the modification effect of soil genetics and landuse must also be considered.
Keywords: plant opal particles; phytolith; chernozem and alkaline soils